Photosynthetic carbon isotope discrimination and its relationship to the carbon isotope signals of stem, soil and ecosystem respiration - Wingate, Lisa (The New phytologist, 2010)
© The Authors (2010). Journal compilation © New Phytologist Trust (2010).